Characterization of dust-related new particle formation events based on long-term measurement in the North China Plain - Shen, Xiaojing; Sun, Junying; Che, Huizheng; Zhang, Yangmei; Zhou, Chunhong; Gui, Ke; Xu, Wanyun; Liu, Quan; Zhong, Junting; Xia, Can; Hu, Xinyao; Zhang, Sinan; et al. (Atmospheric chemistry and physics, 2023)
Mineral dust is a major natural atmospheric aerosol that impacts the Earth's radiation balance. The significant scavenging process of fine particles by the strong wind during the dust episodes provided a relatively clean environment that was favourable for new particle formation (NPF) occurrence. In this study, the NPF occurred following the dust episodes (dust-related NPF), and other cases under clean and polluted conditions were classified based on the long-term particle number size distribution (PNSD) in urban Beijing in spring from 2017 to 2021. It was found that the observed formation (Jobs) and growth rate (GR) of dust-related NPF events were approximately 50 % and 30 % lower than the values of other NPF days, respectively. A typical severe dust storm that originated from Mongolia and swept over northern China on 15–16 March 2021 was analysed, to illustrate how the dust storm influences the NPF event. The maximum hourly mean PM10 mass concentration reached 8000 µg m−3 during this dust storm. The occurrence of an NPF event after a dust storm was facilitated due to the low condensation sink (∼ 0.005 s−1) caused by the strong dilution process of pre-existing particles. However, a downward trend of particle hygroscopicity was found during dust storm and NPF event as compared with the polluted episode, resulting in an increasing trend of the critical diameter at different supersaturations (ss), where aerosols are activated as cloud condensation nuclei (CCN), although the NPF event occurred when dust faded. The critical diameter was elevated by approximately 6 %–10 % (ss = 0.2 % and 0.7 %) during the dust storm, resulting in a lower CCN activation ratio, especially at low supersaturation. Modifications of the nucleation and growth process, as well as the particle-size distribution and hygroscopicity of the dust particles, provide valuable information that reveals the underlying climate and air quality effects of Asian mineral dust.